A bibliometric exploration of affective factors in mathematics education: research trends, thematic evolution, and topic modeling - Taştepe, Mehtap; Özkaya, Abdulkadir (Frontiers in Psychology, 2026)
This study aims to examine research trends in the field of affective factors in mathematics education between 1978 and 2025 using trend topic analysis. A total of 2,587 articles systematically collected from the Web of Science and Scopus databases were analyzed using topic modeling, hierarchical clustering, and multidimensional scaling techniques. The findings reveal that the volume of research in the field has steadily increased, but there has been a shift in thematic focus from broad topics to more specific and contextual areas. While “math anxiety” emerged as the most dominant research focus, teachers’ affective characteristics (Topic 4) and math anxiety (Topic 6) were the fastest growing themes in recent years. In contrast, the intersection of technology and materials with affective factors (Topic 1) and positive psychology-focused concepts (enjoyment, curiosity, flow) have been insufficiently researched. Hierarchical clustering showed that the topics fell into two main clusters: teaching/achievement-focused (Topics 2, 4, 5, 6) and context-factor-focused (Topics 1, 3, 7). The study highlights the asymmetric distribution and research gaps in the field, suggesting that future studies should focus on areas such as positive psychology, integrated theoretical models, and technology-based interventions. Furthermore, the importance of teacher training and math anxiety intervention programs is emphasized.